Characteristics of Urban Heat Island Condition in DKI Jakarta - Siti Badriyah Rushayati; Rachmad Hermawan (Forum Geografi, 2013)
DKI Jakarta area with high CO2 emission and 84,95 % of  built-up areas (year of 2009) cause urban heat island (UHI).  To overcome UHI problems, its characteristics must be known.  Trend analysis of surface temperature areas was conducted by comparison of surface temperature  spatial distribution of 2006 with 2010.  UHI analysis based on geograpical coordinates were also conducted.  High surface temperature of 34 ºC was on inner city and decreasing to sub urban area.  High surface temperature were especially on high density bulit-up areas. Priority of  solving UHI problems are conducted on high surface temperature areas.